FAKTOR EKSTERNAL DALAM PENENTUAN STRATEGI DASAR PROGRAM PENDIDIKAN BIDANG REKAYASA LOGISTIK DAN RANTAI SUPLAI - Rio Aurachman (Politeknik APP Jakarta, 2018)
Abstract In planning education strategies in the field of logistics and SCM, external factors evaluation approach can be implemented. This study proposes the approach of mass media sources and latest news as a basis for determining external factors, as a result, the formulation obtained is newest and more contextual. Those external factors then are going to be analyzed to formulate a strategy that is suitable for logistics education. The strategy emerges into several main things; although it is not time to lead fully to Industry 4.0, the Education curriculum should include knowledge that is aligned and supports the knowledge, Soft Skills that needed to be in logistics and supply chain education are English language skills and the ability to search for data. Object of the research in terms of logistics education which currently growing interests are namely logistics and SCM marine, e-commerce and international zones. Graduates need to be equipped with the ability to do business process efficiently and digitize all business processes.